2019
DOI: 10.3390/biom9070285
|View full text |Cite
|
Sign up to set email alerts
|

Phytohormones Regulate Accumulation of Osmolytes Under Abiotic Stress

Abstract: Plants face a variety of abiotic stresses, which generate reactive oxygen species (ROS), and ultimately obstruct normal growth and development of plants. To prevent cellular damage caused by oxidative stress, plants accumulate certain compatible solutes known as osmolytes to safeguard the cellular machinery. The most common osmolytes that play crucial role in osmoregulation are proline, glycine-betaine, polyamines, and sugars. These compounds stabilize the osmotic differences between surroundings of cell and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
239
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 470 publications
(282 citation statements)
references
References 299 publications
(369 reference statements)
6
239
2
Order By: Relevance
“…Low temperatures could decrease level of Ros in study, in which results were inconsistent with Sharma(Sharma, Shahzad, Kumar, et al, 2019;Sharma, Shahzad, Rehman, et al, 2019), due to different species possibly.Forty-seven annotated DEGs were identified in photosynthesis and Ros pathways between CKL and U3. Bar graph indicating the DEGs among the sets of CK_VS_CKL and CKL_VS_U3 (a).…”
contrasting
confidence: 58%
See 2 more Smart Citations
“…Low temperatures could decrease level of Ros in study, in which results were inconsistent with Sharma(Sharma, Shahzad, Kumar, et al, 2019;Sharma, Shahzad, Rehman, et al, 2019), due to different species possibly.Forty-seven annotated DEGs were identified in photosynthesis and Ros pathways between CKL and U3. Bar graph indicating the DEGs among the sets of CK_VS_CKL and CKL_VS_U3 (a).…”
contrasting
confidence: 58%
“…Among these DEGs, most genes were down-regulated genes. Low temperatures could decrease level of Ros in study, in which results were inconsistent with Sharma(Sharma, Shahzad, Kumar, et al, 2019;Sharma, Shahzad, Rehman, et al, 2019), due to different species possibly.Forty-seven annotated DEGs were identified in photosynthesis and Ros pathways between CKL and U3. Among them, chloroplastic, peroxidase 2 and peroxidase 12, pyruvate, phosphate dikinase 2 isoform X1, peroxidase N OS = Armoracia rusticana, peroxisomal (S)-2-hydroxy-acid oxidase GLO3, peroxidase 52, peroxidase 21, and peroxidase 54 were significantly up-regulated.…”
contrasting
confidence: 58%
See 1 more Smart Citation
“…Apart from ion homeostasis, proline, and sugar accumulation is another well-known mechanism that has evolved in many plant species to overcome salt stress. The accumulation of sugars and proline in salt stress conditions protects the cells by balancing the osmotic strength of the cytosol with that of the vacuole and the external environment [51,52]. Furthermore, proline has a double role in enhancing salt-stress tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Liu [63] reported that BL treatment promoted the activity of antioxidant enzymes in Chorispora bungeana and increased the content of proline and glutathione under chilling stress, thereby eliminating excess ROS. More studies have shown that appropriate concentrations of BL can significantly increase antioxidant enzyme activity and increase antioxidant defense [20,[64][65][66]. However, after spraying three concentrations (T1, T2, T3) of BL solution onto two maize hybrids under chilling stress, the MDA content of the seedlings decreased significantly, and the antioxidant enzyme activity increased significantly.…”
Section: Protective Effects Of Blmentioning
confidence: 99%